Health-related quality of life among prostate cancer patients: real-life situation at the beginning of treatment. (2nd January 2017) - Bergius, Susanne; Torvinen, Saku; Muhonen, Timo; Roine, Risto P.; Sintonen, Harri; Taari, Kimmo
Abstract: Objective: The aims of this study were to measure the real-life health-related quality of life (HRQoL) of newly diagnosed prostate cancer (PCa) patients, to compare it with that of the general male population and to explore factors affecting HRQoL. Methods: All newly diagnosed PCa patients in the Helsinki University Hospital were asked to fill in 15D and EORTC QLQ-C30 questionnaires. Clinical background information was collected retrospectively from patient charts. Patients were categorized into three mutually exclusive groups based on the disease stage: Local, Locally advanced and Metastatic groups. Multivariate linear regression analysis was conducted to explore which factors explained variance in 15D scores. A regression model was built to map the EORTC QLQ-C30 to 15D in a random sample of 50% of patients and the model was tested in the other half of the patients. Results: In total, 1050 men with a mean age of 67 years responded to the questionnaires. The mean ± SD 15D score of patients was slightly lower than that of the age-standardized general male population: 0.905 ± 0.089 vs 0.915 ± 0.082 ( p = .057). The mean ± SD 15D utility scores were 0.912 ± 0.084, 0.897 ± 0.102 and 0.855 ± 0.109 for Local, Locally advanced and Metastatic groups, respectively. The mapping model of EORTC QLQ-C30 to 15D was robust and fitted well (root mean square error = 0.042, adjusted R ² = .79). Conclusions: The HRQoL of PCa patients entering treatment was similar to that of the general population. HRQoL was most impaired among patients with metastatic disease, whereas the difference between patients with localized PCa and the general population was minor. Mapping indicated that the 15D score aggregates quite accurately the information from the EORTC QLQ-C30.